2018
DOI: 10.20960/nh.1794
|View full text |Cite
|
Sign up to set email alerts
|

Health-related physical fitness of normal, stunted and overweight children aged 6-14 years in Macedonia

Abstract: Introducción: la nutrición parenteral (NP) en la infancia es un tratamiento cuyas características son muy variables en función de la edad y la patología que presente el paciente.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
6
6
0
2
Order By: Relevance
“…Consistent with previous literature findings, the present study detected statistically significant differences between various physical fitness scores achieved by OB, OW, NW and UW children. Specifically, it is known that OW and OB children perform worse than NW children in weight bearing activities, as was the case in the Leger, shuttle and jump tests [16][17][18][19][20][21][22][23][24][25]. In the present study, this trend was found to be similar between sexes and more prominent in older children than in younger children, emphasizing the need to promote healthier lifestyles from an early age.…”
Section: Plos Onesupporting
confidence: 62%
See 4 more Smart Citations
“…Consistent with previous literature findings, the present study detected statistically significant differences between various physical fitness scores achieved by OB, OW, NW and UW children. Specifically, it is known that OW and OB children perform worse than NW children in weight bearing activities, as was the case in the Leger, shuttle and jump tests [16][17][18][19][20][21][22][23][24][25]. In the present study, this trend was found to be similar between sexes and more prominent in older children than in younger children, emphasizing the need to promote healthier lifestyles from an early age.…”
Section: Plos Onesupporting
confidence: 62%
“…On the other hand, the increased mechanical work needed to lift the body off the ground in everydaylife activities could have a positive influence on absolute muscle strength, increasing fat free mass (FFM) more in OB children than in their NW counterparts [53,54]. A higher FFM, which is known to correlate with strength parameters in obese subjects [55], might be the reason why better throwing scores were obtained by the OB and OW children in the present and in previous studies [18,20,21,24] than by NW children. In contrast, some authors [23,25] have found comparable strength of the upper limb in OB, OW and NW children.…”
Section: Plos Onementioning
confidence: 46%
See 3 more Smart Citations